This Year, a Witch! - Abbott, Zoey (New York : Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2025)
A little girl is tired of dressing up as something adorable for Halloween, so this year she plans to be a scary witch and frighten everyone, even herself.
new kids book 2025 summer.
Ages 4-8
Grades K-1
Keywords: Girls -- Juvenile fiction; Halloween -- Juvenile fiction; Halloween costumes -- Juvenile fiction; Witches -- Juvenile fiction; Costume -- Fiction; Girls -- Fiction; Halloween -- Fiction; Witches -- Fiction; Picture books